A High-Throughput Method as a Diagnostic Tool for HIV Detection in Patient-Specific Induced Pluripotent Stem Cells Generated by Different Reprogramming Methods - Daniela Hübscher; Sabine Rebs; Luis Haupt; Thomas Borchert; Celina Isabell Guessoum; Franziska Treu; Steffen Köhne; Andreas Maus; Mario Hambrecht; Samuel Sossalla; Ralf Dressel; Angela Uy; et al. (Stem Cells International)
Induced pluripotent stem cells (iPSCs) provide a unique opportunity for generation of patient-specific cells for use in translational purposes. We aimed to compare iPSCs generated by different reprogramming methods regarding their reprogramming efficiency, pluripotency capacity, and the possibility to use high-throughput PCR-based methods for detection of human pathogenic viruses. iPSCs from skin fibroblasts (FB), peripheral blood mononuclear cells (PBMCs), or mesenchymal stem cells (MSCs) were generated by using three different reprogramming systems including chromosomal integrating and nonintegrating methods. Reprogramming efficiencies were in accordance with the literature, indicating that the parental cell type and the reprogramming method play a major role for the reprogramming efficiencies (FB: STEMCCA: 1.30±0.18, Sendai virus: 1.37±0.01, and episomal plasmids: 0.04±0.02; PBMCs: Sendai virus: 0.002±0.001, episomal plasmids: 0) but result in the same characteristics of pluripotency. We found the highest reprogramming efficiencies for MSC with 3.32±1.2 by using episomal plasmids. Since GMP standard working procedures and screening units need virus contamination-free cell lines, we studied HIV-1 contamination in the generated iPSCs. We used the high-throughput cobas® 6800/8800 system, which is normally used for detection of HIV-1 in plasma of patients, and found that footprint-free reprogramming methods as episomal plasmids and Sendai virus are useful for the described virus detection method. This fast, cost-effective, robust, and reliable assay demonstrates the feasibility to use high-throughput PCR-based methods for detection of human pathogenic viruses in ps-iPSC lines that were generated with nongenome integrating reprogramming methods.